Application technology evaluation system of green building of student apartment in Central Plains area-Take Xinzheng City as an example - YunLiang, Niu; Azhaili, Baharun; Mohd Afzan, Mohamed (Ministry of Education, china and Northeastern University, china, 2024)
Taking Xinzheng City as an example, this study deeply discusses the application technology and evaluation system of green building of student apartment, aiming to scientifically guide the green transformation of student apartment, realize energy conservation, environmental protection and efficient utilization of resources, and promote the sustainable development of the construction industry. First of all, the construction principle of the evaluation system is determined, and the evaluation principle of scientific and reasonable, simple operation and easy to popularize is established, focusing on the comprehensive evaluation of energy conservation, environmental protection, building materials and indoor environment. Through literature review and field research, the evaluation index system of energy efficiency utilization, water resource management, material utilization, indoor environmental quality and innovative management was established. Using the method of combining qualitative and quantitative, the application status of green building in Xinzheng student apartment is deeply analyzed through expert consultation, questionnaire survey and on-site evaluation. The evaluation results show that the implementation of green building technology effectively reduces energy consumption, reduces environmental pollution, and significantly improves the living comfort and health level. The research innovation point lies in the green building evaluation system suitable for student apartments in the Central Plains, which has the characteristics of regional adaptability and outstanding resource utilization efficiency and indoor environment quality. Moreover, this study presents a series of targeted strategies and suggestions to provide scientific basis and operational guidance for the green transformation of student apartments. Conclusion, the important role of green building in promoting the sustainable development of the construction industry and promoting the sustainable development of social economy is emphasized. Through the establishment and application of a scientific and reasonable evaluation system, it promotes the application of green building technology in student apartments, and provides reference for other types of buildings, promotes the green transformation of the whole construction industry, and realizes the goals of energy conservation, emission reduction and sustainable development. The research results are expected to provide theoretical reference and practical guidance for policy formulation, technological innovation and market promotion in the field of green building, and are of great significance to promoting the green transformation and sustainable development of the construction industry.